(untitled) (Advancements in Homeopathic Research, 2025)
Background-Skin is the mirror of internal health, any disturbance in here reflects on skin which is very worrying. Psoriasis is one of the non communicable chronic skin disease. Though non fatal bur its recurrence and complications make people suffer a lot. The real cause is yet to be discovered. A study conducted on global burden of disease in 2010 and 2014 showed that 4th leading cause of non-fatal morbidity were skin diseases worldwide. Objective-Present study is an attempt-to understand the mental/emotional factors which trigger/aggravate the psoriasis. Methodology-Purposive sampling method was used to select subjects based on inclusion/exclusion criterion. A detailed individual case taking was done to understand the triggering/aggravating factors at mental/emotional level. Results-In this study it was found that loss of loved ones (20%) and suppressed anger (20%) as a main triggering factors. The most common age group affected was 21-30years (40%), Conclusion-though with this we cannot conclude these are the sole triggering factors, there may be more as in homoeopathy advocates individualization as one of the basic fundamental principles, and it is recommended to study with large samples.